2016
DOI: 10.1513/annalsats.201605-342bc
|View full text |Cite
|
Sign up to set email alerts
|

Wearable In-Ear Encephalography Sensor for Monitoring Sleep. Preliminary Observations from Nap Studies

Abstract: Substantial agreement was observed between recordings derived from a new ear-EEG sensor and conventional scalp electrodes on four healthy volunteers during daytime naps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 16 publications
1
59
0
Order By: Relevance
“…An elegant solution to avoid placing electrodes on the head in locations where they are visible or difficult to apply, has been proposed in the form of a miniaturized EEG device placed in or around the ears, offering both a reliable and user-friendly alternative for full-scalp EEG (Mikkelsen, Kappel, Mandic, & Kidmose, 2015;Mikkelsen, Kidmose, & Hansen, 2017;Mikkelsen, Villadsen, Otto, & Kidmose, 2017;Pacharra, Debener, & Wascher, 2017). More specifically, several studies have reported progress towards using such ear-centered EEG devices for tracking the presence of different sleep stages (Looney, Goverdovsky, Rosenzwei, Morrell, & Mandic, 2016;Mikkelsen, Villadsen, et al, 2017;Stochholm, Mikkelsen, & Kidmose, 2016;Zibrandtsen, Kidmose, Otto, Ibsen, & Kjaer, 2016). These studies all showed promising results, but involved a limited number of participants and also restricted electrode positioning.…”
Section: Introductionmentioning
confidence: 99%
“…An elegant solution to avoid placing electrodes on the head in locations where they are visible or difficult to apply, has been proposed in the form of a miniaturized EEG device placed in or around the ears, offering both a reliable and user-friendly alternative for full-scalp EEG (Mikkelsen, Kappel, Mandic, & Kidmose, 2015;Mikkelsen, Kidmose, & Hansen, 2017;Mikkelsen, Villadsen, Otto, & Kidmose, 2017;Pacharra, Debener, & Wascher, 2017). More specifically, several studies have reported progress towards using such ear-centered EEG devices for tracking the presence of different sleep stages (Looney, Goverdovsky, Rosenzwei, Morrell, & Mandic, 2016;Mikkelsen, Villadsen, et al, 2017;Stochholm, Mikkelsen, & Kidmose, 2016;Zibrandtsen, Kidmose, Otto, Ibsen, & Kjaer, 2016). These studies all showed promising results, but involved a limited number of participants and also restricted electrode positioning.…”
Section: Introductionmentioning
confidence: 99%
“…Classification performance was evaluated for both scalp-EEG and ear-EEG patterns, and showed that ear-EEG is similarly informative to scalp-EEG to predict sleep stages, which were labelled from a manually scored hypnogram from conventional PSG recording. With a different perspective, our recent study [11] performed simultaneous sleep monitoring from four subjects, using both scalp- and ear-EEG data channels, and reported Substantial Agreement between the corresponding hypnograms, manually and blindly scored by a trained clinician, as shown in Figure 2A. The in-ear EEG data were recorded from our novel ‘one-fits-all’ generic viscoelastic earpieces [16].…”
Section: Introductionmentioning
confidence: 99%
“…For rigour, the ear-EEG automatic scoring procedures were validated for the following scenarios:

Agreement between automatically predicted sleep stages based on ear-EEG patterns and the manually scored hypnogram from ear-EEG ( Scenario 1 ).

Agreement between automatically predicted sleep stages based on ear-EEG patterns and the manually scored hypnogram from scalp-EEG ( Scenario 2 ).

Figure 2B illustrates the proposed analysis framework. The results are benchmarked against the results in [11] where both the scalp- and ear-EEG hypnograms were scored manually. In this way, we establish a proof-of-concept for the feasibility of ear-EEG in automatic scoring of sleep patterns out-of-clinic and in the community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Wearable technologies to diagnose obstructive sleep apnoea (OSA) : Wearable technologies are increasingly being used to monitor various aspects of health, including sleep . Validation studies on wrist‐worn devices suggest that we are rapidly moving towards devices that can reliably monitor and stage sleep .…”
Section: New Diagnosticsmentioning
confidence: 99%